2010
DOI: 10.15282/ijame.2.2010.7.0015
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Surface Properties in Manganese Powder Mixed Electrical Discharge Machining of OHNS And D2 Die Steels

Abstract: The electrical discharge machining (EDM) process is used for generating accurate internal profiles in hardened materials. An powder additive in the hydrocarbon dielectric affects the energy distribution and sparking efficiency, and consequently the surface finish and micro-hardness. In this paper the Taguchi approach has been used to optimize and compare the surface properties in manganese powder-mixed EDM of oil-hardening non-shrinkable (OHNS) and high-carbon high-chromium (D2) die steels. The results of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…The die sinking electrical discharge machining is the most widely used techniques for replication of products such as die-casting, injection moulding, etc [73][74][75]. It is also better known as the cavity type EDM or volume EDM.…”
Section: Die Sinking Edmmentioning
confidence: 99%
“…The die sinking electrical discharge machining is the most widely used techniques for replication of products such as die-casting, injection moulding, etc [73][74][75]. It is also better known as the cavity type EDM or volume EDM.…”
Section: Die Sinking Edmmentioning
confidence: 99%
“…In addition to these difficulties, the higher cost of these special tools limits the conventional machining of titanium alloys. Although the above-mentioned tool materials seem to be effective in machining, they cannot be recommended for the machining of titanium and its alloys (Hascalik, Caydas, & Gurun, 2007;Kumar & Singh, 2010;Singh & Singh, 2011). It is recognized that electrical discharge machining can be used effectively in machining hard, high-strength, and temperature-resistant materials (Khan, Rahman, Kadirgama, Maleque, & Ishak, 2011c;Najiha, Rahman, Kamal, Yusoff, & Kadirgama, 2012;Yusoff, Mohamed Suffian, & Taib, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The surface integrity is thus given great attention during machining. It is reported that thermal and mechanical cycling, microstructural transformations, and mechanical and thermal deformations during machining processes are caused by these impacts (Axinte & Dewes, 2002;Kumar & Singh, 2010;Singh & Singh, 2011). In any case where the fatigue life of a machined part is deemed central, the smoothest possible surface is important (Novovic, Dewes, Aspinwall, Voice, & Bowen, 2004).…”
Section: Introductionmentioning
confidence: 99%